Efficacy and safety of YQFM (YiQiFuMai lyophilized injection) on acute ischemic stroke (FAST): rationale and design for a randomized, double-blind, placebo-controlled trial - Yingzhi Xu; Li Sun; Zhaoyou Meng; Xinxing Lai; Dayong Ma; Yuqiu An; Boxuan Du; Qiaosheng Ren; Ying Gao; Kegang Cao (BMC Complementary Medicine and Therapies)
Abstract Background Low blood pressure at acute ischemic stroke onset is associated with both short- and long-term adverse outcomes. Studies have shown that YQFM (YiQiFuMai lyophilized injection) can ameliorate neurological deficits in ischemic stroke.However, all of these studies are all small-sample clinical observations lacking rigorous study design for AIS with inappropriate blood pressure. Aims To describe the design of the YQFM aimed at reducing the disability rate in AIS patients with inappropriate blood pressure. Methods This trial is a prospective, multicenter, randomized, double-blind, placebo-controlled, superiority trial aimed at evaluating the efficacy and safety of YQFM in reducing the disability rate in patients with acute hypoperfusion stroke within 90 days. We will recruit 480 patients with AIS within 48 h of symptom onset from 24 hospitals, who have large atherosclerosis, systolic pressure ≤ 155 mmHg, and an NIHSS score of 4–18. Eligible patients will be randomly assigned to receive either YQFM or 0.9% NaCl injection once daily for 10 days and will be followed up until the 90th day after stroke onset.The primary outcome will be the proportion of patients with mRS ≤ 2 at 90 days after patient recruitment. Secondary outcomes will include the proportion of early neurological deterioration at 7 days, patient self-reported outcomes and the syndrome score at 10 days, MMSE scale and BI scale at 90 days.During the trial, adverse events will be recorded. These data will be analyzed according to the predetermined statistical analysis plan. Conclusion This study is the first randomized controlled double-blind trial to evaluate the efficacy and safety of YQFM in patients with AIS. This trial will provide evidence-based data for YQFM application in AIS with inappropriate blood pressure. Clinical trial registration ChiCTR2300074125 was registered on 31 July, 2023. For more information, please visit Clinical Trials.gov at https://www.chictr.org.cn/showproj.html?Proj=200686 . Graphical Abstract